The Role of Periodontal Maintenance in Long-Term Dental Health: A Guide to Supportive Periodontal Therapy - Banerjee, Dr. Madhulika; Dr. Janardhana Amaranath B.J.; Das, Dr. Neelam; Sharma, Dr. Rajat; Meetika, Dr.; Gahlot, Dr. Deepshikha; Sihani, Dr. Komal; Grover, Dr. Ramanjeet Kaur; Shikha, Dr.; Sharma, Dr. Shantanu (The Role of Periodontal Maintenance in Long-Term Dental Health: A Guide to Supportive Periodontal Therapy, Edition 1, 2024)
Periodontitis is a chronic inflammatory disease induced by bacteria, leading to the destruction of the connective tissues and bone that support teeth. Active periodontal treatment focuses on reducing the inflammatory response by eradicating bacterial deposits. Once treatment is completed and inflammation is arrested, Supportive Periodontal Therapy (SPT) is crucial in reducing the probability of reinfection and disease progression. SPT aims to maintain teeth without pain, excessive mobility, or persistent infection over the long term and to prevent related oral diseases. This comprehensive approach involves updating medical and dental histories, radiographic reviews, and thorough examinations of both extraoral and intraoral soft tissues. It includes dental assessments, periodontal evaluations, and the meticulous removal of bacterial plaque and calculus from both supragingival and subgingival areas. Its fundamental role in sustaining both oral and overall health cannot be overstated, making it an essential practice for both patients and dentists/periodontists. This book assesses the success of SPT, drawing on findings from various long-term, studies. It underscores the essential role of therapeutic measures in supporting patients' efforts to control periodontal infections and maintain both oral and overall health.